On National or Supranational Objectives Improving the Effectiveness of Targeted Expenditure Programs - Zhang, Ping (International Monetary Fund, 2002)
Central governments or the international community at large are concerned about subnational service delivery. The design of targeted expenditure programs features frequently in central efforts to redistribute infrastructure and social spending or assure minimum standards. These programs are typically financed by the center, often with external assistance, but are implemented at the subnational level, which may not have incentives to spend the resources as intended by the center or donors. We discuss mechanisms for improving the effectiveness of targeted public expenditure programs, modeling the interaction between different levels of government as a dynamic game. An incentive structure could be designed that compelled local governments to truthfully reveal their ability to implement national programs in a cost-effective manner and to exert the effort required to maximize the expected benefits. The models have direct policy relevance in the Heavily Indebted Poor Countries (HIPCs), where donor-financed resources are used for poverty-reduction at the local level, or in large countries such as China, where there is an effort to redirect social and infrastructure spending to particular regions